Hydrological connectivity: improving coastal literacy and resilience in classrooms and communities in the City of Wilmington - Bresnahan, Philip Joseph; Hovis, Meredith; Frensley, B. Troy; Polk, Mariko; Moran, Erin; Harris, Craig; Lebby, Kimberly; Settin, Bentley; Davidson, Jordan; Kasney, Chelsea; Anderson, Steven; O’Connor, Chris; et al. (Frontiers in Water, 2026)
Coastal flooding creates regular and episodic hazards—both of which are worsening due to sea-level rise, changing precipitation patterns, land-use changes, subsidence, and more—with varying degrees of predictability. The heterogeneity of flooding over space and time creates challenges in monitoring, modeling, communication of, and preparation for risks. Improving coastal community preparedness and resiliency requires a multi-pronged approach, including, for example, better monitoring and alerting paired with location-specific awareness of flood risk and safety measures. In this Hydrological Connectivity project, an academic-government-nonprofit-community collaborative team worked together to (1) find and fill gaps in real-time flood monitoring and alerting, (2) listen to community concerns and needs and provide flood safety strategies, and (3) foster intergenerational learning by teaching 4th grade students in the community about coastal hydrology and flood monitoring techniques through place- and project-based learning. This manuscript describes the need for and deployment of this multi-partner and multidisciplinary approach to improving coastal literacy and resilience in a frontline community in Wilmington, NC, United States, and our lessons learned.